The Impact of Radicalism toward National Defense - I Wayan Midhio; Ahwan Ismadi; Ate Ajat Waluyo (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2017)
This study aims to analyze radicalism impact toward national defense. The method used is descriptive qualitative, data collection techniques such as observation, interviews, documentation, and literature. Processing of research data according Miles and Huberman. The results showed that implementation of the Territorial Development by District Military Command 0621 Bogor Regency through territorial management of Planning and Control Systems Development of Territories & Management of Territorial Development were able to map the potential and vulnerability of the area ie geography areas, demographic and social conditions so that development of radicalism could be prevented